Stakeholders, Service, and the Future of University Press Publishing - Brown, Richard (Journal of Scholarly Publishing, 2013)
Stakeholder theory is a useful framework for understanding any industry, and I contend that university presses should focus their energies and attention on managing stakeholders and creating value for stakeholders. But while this focus is necessary, it is not sufficient. I propose that a commitment to service through entrepreneurship underlies university press relationships with primary stakeholders. University presses should therefore (a) strategically seek the widest possible access for value-added content through (b) creative delivery channels in order to help scholarly communities of practice advance their teaching, learning, and research. This will, I hope, (d) result in sufficient revenue to allow the organization to grow and flourish (e) in order to serve communities of practice and the academy and society more effectively.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEzOC9qc3AuNDQuMi4wMDE